Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1053/jhep.2002.31870
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic HCV RNA before and after treatment with interferon alone or combined with ribavirin

Abstract: The clinical use of measuring hepatic hepatitis C virus (HCV) RNA before and after therapy in patients with chronic hepatitis C has been assessed in a number of small clinical trials. Viral clearance from the liver may be a better marker of long-term response than eradication of serum HCV RNA. The aim of this study was to evaluate quantitative hepatic HCV-RNA measurements before and after antiviral therapy. Two thousand eighty-nine chronic hepatitis C patients were enrolled in 3 published clinical trials evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 31 publications
(50 reference statements)
2
86
1
1
Order By: Relevance
“…This conclusion is supported by a recent analysis that similarly failed to detect PBMC-associated HCV RNA in 9 spontaneous and 2 treatment-induced aviremic patients. 16 A greater than 90% rate of clearance of HCV RNA in the liver of sustained virological response also indicates that a long-lived hepatic reservoir is unlikely to exist, [37][38][39] although another report detected hepatic HCV RNA in 50% of spontaneously aviremic seropositive subjects. 22 The slow decrease in anti-HCV antibody titers in subjects with spontaneously cleared viremia [40][41][42][43][44] as well as the complete seroreversion detected in 7% of transfusion-transmitted infections 5 may also reflect an absence of ongoing antigenic stimulation, indirectly supporting clearance of infection in persons who test HCV RNA-negative in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by a recent analysis that similarly failed to detect PBMC-associated HCV RNA in 9 spontaneous and 2 treatment-induced aviremic patients. 16 A greater than 90% rate of clearance of HCV RNA in the liver of sustained virological response also indicates that a long-lived hepatic reservoir is unlikely to exist, [37][38][39] although another report detected hepatic HCV RNA in 50% of spontaneously aviremic seropositive subjects. 22 The slow decrease in anti-HCV antibody titers in subjects with spontaneously cleared viremia [40][41][42][43][44] as well as the complete seroreversion detected in 7% of transfusion-transmitted infections 5 may also reflect an absence of ongoing antigenic stimulation, indirectly supporting clearance of infection in persons who test HCV RNA-negative in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral treatments are becoming more and more efficient, and monitoring of therapy requires reliable viral quantification tests. Hepatitis C virus (HCV) is an important cause of chronic liver disease, and recent studies have shown the efficiency of a combination of pegylated interferon and ribavirin in the treatment of patients with chronic hepatitis C (7,9). Furthermore, several studies have shown that the HCV genotype and viral load prior to treatment have predictive values for the response to antiviral therapy and that measurement of serum HCV RNA levels is useful in the monitoring of treated patients (2,5,8).…”
Section: Before Initiating New Large-scale Therapeutic Trials For Hepmentioning
confidence: 99%
“…1,2 Patients who test HCV RNA-negative by such assays at least 24 weeks after completion of therapy are considered to have a sustained virological response (SVR), a critical endpoint associated with durable eradication of infection and long-term remission, if not cure, of disease. [3][4][5][6] HCV RNA testing during therapy is also helpful for indicating whether a virological response has occurred and for predicting the likelihood of an eventual SVR with prolongation of therapy. Current management guidelines include the recommendation that patients treated with pegylated interferon alpha (peginterferon) and ribavirin have therapy stopped if HCV RNA is still present after 24 weeks of treatment.…”
mentioning
confidence: 99%